Strength of soft clay reinforced with 10 mm single crushed coconut shell (CCS) column - Muzamir, Hasan; Ieszaliana, Ali; Hyodo, Masayuki (GEOMATE International Society, 2019)
Stone column can be used as a ground improvement technique where a portion of soft soil is replaced with granular material such as stone or sand. The benefit of using stone columns in low strength soil has been proven as an efficient method to improve the bearing capacity and reduce settlement of soft soils. This study aims to investigate the improvement in shear strength of soft clay by embedded with a single crushed coconut shell (CCS) column. The cost of soil improvement can be reduced because of CCS is a waste material. This paper was done by determining the physical and mechanical properties of kaolin and CCS as well as the effect of height penetration ratio of a single CCS column on shear strength characteristics. Unconfined Compression Test (UCT) was conducted for 4 batch kaolin samples including a control sample in order to determine the shear strength. Each batch involved four samples to find the accurate value. The research variables are the height of crushed coconut shell column which is 60 mm, 80 mm and 100 mm where the column penetration ratio is 0.60, 0.80 and 1.00 respectively. A total of 16 unconfined compression tests had been conducted on kaolin sample with dimensions of 50mm in diameter and 100 mm in height. The increment of shear strength by embedded with crushed coconut shell columns is 19.02 %, 34.76 % and 24.34 % for with 4 % area displacement ratio at column penetration ratio of 0.60, 0.80 and 1.00 respectively. From the results obtained, the relationship between shear strength increases is influenced by the height of the column. The maximum column height (full penetration) does not generate the highest strength and it proves that "critical column length" theory is true in this study.